MEMBANGUN BADAN PUBLIK YANG TRANSPARAN DAN AKUNTABEL DENGAN MEMBUDAYAKAN KESADARAN BERKONSTITUSI - Sukriono, Didik (JURNAL KONSTITUSI, 2011)
Substitution for several times of national and local leader, which should to became historical momentum to well held of social arrangement, economic arrangement, and better new political arrangement. But exactly on the contrary that is tending the increasing of